Brigham Fracture Intervention Team Initiatives for Hospital Patients with Hip Fractures: A Paradigm Shift. (17th August 2009) - Glowacki, Julie; Harris, Mitchel B.; Simon, Josef; Wright, John; Kolatkar, Nikheel S.; Thornhill, Thomas S.; LeBoff, Meryl S.
Abstract : We designed, implemented, and revised the Brigham Fracture Intervention Team (B-FIT) initiatives to improve in-hospital care of fracture (Fx) patients. Effectiveness was evaluated for 181 medical records of 4 cohorts in four successive years of consecutive patients who were admitted with a fragility hip Fx. The Discharge Initiative (DI) (computer-based) includes 1200 mg calcium and 1000 IU vitaminD 3 daily. The Admission Initiative (AI) was introduced one year later with reminders for serum 25OHD measurement, initiation of daily calcium (1200 mg) and vitamin D (800 IU), and an order for Endocrinology consultation, with an amendment for a computer-assisted reminder and a dose ofD 2 (50 000 IU). Initially, the computer-based DI was more effective (67%) than the surgeon-driven AI (33%, P < .001 ). After introduction of a computer-assisted reminder, AI effectiveness increased to 68%. The marked prevalence of vitamin D insufficiency reaffirms the importance of incorporating vitamin D recommendations in Fx care pathways.